2016
DOI: 10.1155/2016/4847812
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Inhibits Advanced Glycation End Products-Induced Inflammatory Response in Murine Macrophages Partly through AMPK Activation and RAGE/NFκB Pathway Suppression

Abstract: Advanced glycation end products (AGEs) are major inflammatory mediators in diabetes, affecting atherosclerosis progression via macrophages. Metformin slows diabetic atherosclerosis progression through mechanisms that remain to be fully elucidated. The present study of murine bone marrow derived macrophages showed that (1) AGEs enhanced proinflammatory cytokines (interleukin-1β (IL-1β), IL-6, and tumor necrosis factor-α (TNF-α)) mRNA expression, RAGE expression, and NFκB activation; (2) metformin pretreatment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
69
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 31 publications
4
69
0
5
Order By: Relevance
“…Using these in vitro models, metformin‐mediated increases in (1) cell proliferation; (2) cell differentiation; (3) insulin‐stimulated glucose uptake; (4) type 1 collagen production; (5) alkaline phosphatase activity; (6) extracellular matrix deposition and mineralization; along with (7) transcriptional up‐regulation of pro‐osteogenic genes (including Runx2 , osteocalcin [ Ocn ], bone morphogenic protein‐2 [ Bmp‐2 ], osteoprotegerin [ Opg ], Igf‐1 ) have been demonstrated in cultured osteoblasts . In vitro, metformin also appears to protect against AGE‐induced cellular injury and cell death in osteoblastic cells, similar to described effects in other human and rodent complication‐affiliated cell types such as neurons, macrophages, cardiomyocytes, and renal tubular cells . In many cases, these effects are thought to be mediated by metformin activation of AMPK signaling pathways .…”
Section: Drugs and Bonementioning
confidence: 99%
“…Using these in vitro models, metformin‐mediated increases in (1) cell proliferation; (2) cell differentiation; (3) insulin‐stimulated glucose uptake; (4) type 1 collagen production; (5) alkaline phosphatase activity; (6) extracellular matrix deposition and mineralization; along with (7) transcriptional up‐regulation of pro‐osteogenic genes (including Runx2 , osteocalcin [ Ocn ], bone morphogenic protein‐2 [ Bmp‐2 ], osteoprotegerin [ Opg ], Igf‐1 ) have been demonstrated in cultured osteoblasts . In vitro, metformin also appears to protect against AGE‐induced cellular injury and cell death in osteoblastic cells, similar to described effects in other human and rodent complication‐affiliated cell types such as neurons, macrophages, cardiomyocytes, and renal tubular cells . In many cases, these effects are thought to be mediated by metformin activation of AMPK signaling pathways .…”
Section: Drugs and Bonementioning
confidence: 99%
“…Activating the AMPK and inhibiting the NF-ⱪB, metformin suppresses the pathway of RAGE/ NF-kB, leading to inhibited effects of AGE and change of phenotype of macrophages from M1 (classical or inflammatory) to M2 (alternatives) by changing the expression of their surface markers (CD86 and CD206, respectively). Finally, the production of inflammatory cytokines and inhibitory cytokines (IL-10) would increase (39). By producing the high mobility group box 1 (HMGB1), which has pseudo-cytokine activity, necrotic cells are able to stimulate many receptors, including TLR4 and RAGE and induce inflammatory responses.…”
Section: Metformin and Inflammatory Markersmentioning
confidence: 99%
“…Mechanisms of antitumor activity of metformin have primarily been attributed to gluconeogenesis inhibition, reduction in insulin concentrations, or suppression of mTORC1 via activation of the AMP-activated protein kinase (AMPK) pathway (15)(16)(17)(18). Recently, it was reported that metformin inhibits inflammatory responses in murine macrophages, in part through AMPK activation and RAGE/NFkB pathway suppression (19). These data suggested that metformin may act on cancer cells, as well as on several host inflammatory and immune cells.…”
mentioning
confidence: 99%